Find the equation of the tangent to the curve y = 3x^2(x+2)^6 at the point (-1,3), in the form y = mx+c

Curve: y = 3x2(x+2)6 Coordinate: (-1, 3)

This is typically a C3/4 level question because of the differentiation, but the rest of the question is possible with year 12 maths knowledge. The best way to tackle this is to find the gradient function of the curve by differentiating, this will give us the gradient of the curve at (-1,3), which is equal to the gradient of the tangent at (-1,3). We then use the equation y-y1=m(x-x1) (where  (x1,y1) = (-1,3) ) to find the equation of the tangent.

Differentiate using the product rule. dy/dx = vu' + uv'

u = 3x2,  v = (x+2)6, u' = 6x, v' = 6(x+2)5

dy/dx = ( (x+2)6 *6x ) +  ( 3x2 * 6(x+2)5) = 6x(x+2)6 + 18x2(x+2)5

When x = -1,

dy/dx = ((6 * -1)(-1 + 2)6) + ((18 * 1) * (-1 + 2)5) = -6 + 18 = 12

y - 3 = 12(x+1)

y = 12x+12+3

y = 12x + 15

Answered by BUNEME K. Maths tutor

11156 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate with respect to x: y=xln(x)


How do you prove by contradiction the irrationality of surds. Use sqrt 2 as an example.


How to sum an arithmetic progression?


What are the different steps involved in Proof by Induction?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences